Regional Development Policies in Turkey in Globalisation Context - ÇELEBİ ZENGİN, Esra (International Journal of Scientific Research and Management (IJSRM), 2018)
The concept of public administration can be defined differently in terms of scope and function, yet generally indicates states’ public policies and the actors of these policies. The extent of the states’ active role in planning and implementation processes of these policies varies according to their ideology in political and economic terms. Nonetheless, regardless of the ideology, it is seen that globalisation and process of change worldwide have led to partial or rooted reform movements in public administration systems. This process is called a transition from traditional public administration to new public administration, and it is based on neoliberal policies. In this new order where states are embracing a more passive role, Turkish public administration experiences this change due to the impact of several factors. The approach followed involves, particularly, coexistence of global and local, and increasing value of privatisations and global actors within the system. A clear reflection of this is seen through principles and strategies embraced within provincial and regional development policies.